Simultaneous Adsorption and Photocatalytic Degradation of Malachite Green Using Electrospun P(3HB)-TiO2 Nanocomposite Fibers and Films - Nanthini Sridewi, Nanthini Sridewi; Lee, Yan Fen; Sudesh, Kumar (Hindawi Publishing Corporation, 2011)
This paper demonstrated the applicability of electrospun P(3HB) film as a dye adsorbent agent.Malachite green (MG) was used as the model dye in this study. Interestingly, the electrospun P(3HB) film exhibited excellent dye adsorption capacity whereby 78% of dye was adsorbed from a 30 μMsolution ofMG. The film was further improvised by incorporating titanium dioxide photocatalysts to form a dual dye treatment system employing adsorption and photocatalytic degradation techniques. The resultant electrospun P(3HB)-50wt% TiO2 was capable of completely decolorizingMGin 45 min under solar irradiation, which corresponded to 58.7% COD removal. The fully decolorizedMG solution also proved to be nontoxic against A. aegypti mosquito larvae. The reapplicability of this film was possible as it induced a decolorization rate of 98% or more at every usage for ten consequent usages. EDX analysis suggested that there were no significant changes in the concentration of titanium (Ti) in the film before and after ten times of usage. The concentration of Ti in cast P(3HB)-50wt%TiO2 film was found to decrease significantly during the repeated usage. The electrospun P(3HB)-50wt%TiO2 film has high potency as an efficient and inexpensive yet simple method for the dye effluent decolorization, degradation, and detoxification.